1995
DOI: 10.1038/ki.1995.35
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intrarenal ACE-inhibition estimated from the renal response to angiotensin I and II in humans

Abstract: Recent studies on the nature of the renin-angiotensin system (RAS) in animals have led to the concept that systemic and intrarenal RAS can be influenced to different degrees by angiotensin converting enzyme (ACE) inhibitors. Assessment of efficacy of intrarenal ACE inhibition by ACE inhibitors in humans is necessarily indirect and has not been reported. We therefore monitored the renal response to acute angiotensin (Ang) I infusion in volunteers taking 20 mg enalapril twice daily, and related the responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The consistency between the lev el of circulating ACE and the renal response to captopril suggests that the intrarenal ACE activity may parallel the circulating ACE activity in normal humans. These find ings agree with the results obtained by Vos et al [12], The present observations could be of paritcular relevance in the interpretation of captopril renograms. Caution may be necessary in interpreting captopril renograms depending on th e ACE/ID polymorphism of the subjects.…”
Section: Figsupporting
confidence: 83%
See 1 more Smart Citation
“…The consistency between the lev el of circulating ACE and the renal response to captopril suggests that the intrarenal ACE activity may parallel the circulating ACE activity in normal humans. These find ings agree with the results obtained by Vos et al [12], The present observations could be of paritcular relevance in the interpretation of captopril renograms. Caution may be necessary in interpreting captopril renograms depending on th e ACE/ID polymorphism of the subjects.…”
Section: Figsupporting
confidence: 83%
“…ERPF (** pp < 0.02), and RVR (*** p < 0.01). no direct methods are currently available to assess renal angiotensin II formation in humans, Voset al [12] evalu ated the efficacy of the ACE inhibitor to block the sys temic and renal angiotensin II formation on the basis of the functional response to angiotensin I and angiotensin II infusion. These authors found close correlations between plasma angiotensin II concentration and MAP, ERPF, and renal sodium handling after both angiotensin I and angiotensin II infusion during ACE inhibition.…”
Section: Figmentioning
confidence: 99%
“…Apart from age, individual susceptibility, genetic factors, implication of multiple biological pathogenic factors, and the lag time between proteinuria appearance and treatment initiation, this insufficient response may be explained by incomplete blockade of the RAS, 51 especially if intrarenal RAS is regulated independently of circulating RAS. 52 The huge amount of renin synthesized and released locally, the limited amount of renal endothelial ACE, 53 the compartmentalization of Ang II in interstitial and tubular fluids, 54 the intrarenal consumption of angiotensinogen, 52 and the uptake of Ang II by the renal AT1Rs 55 influences the intrarenal levels of Ang I and Ang II, which differ from their plasma levels.…”
Section: Azizi and Ménard Combined Blockade Of Renin-angiotensin Systemmentioning
confidence: 99%
“…In studies designed to examine intrarenal ACE function by measuring the renal haemodynamic response to intravenous Ang I in subjects on a high-salt diet, it appeared that ACE in the kidney made a trivial contribution to total Ang II generation. 19,20 Conversely, in studies on a low-salt diet, Figure 1 Increase in renal plasma flow (RPF) in response to blocking the renin-angiotensin system (RAS) with either the ACE inhibitor, captopril, or the AT 1 -receptor blocker, candesartan, in healthy humans studied on either a low-salt (10 mmol/Na/day) or a high-salt (200 mmol/ Na/day) diet. Captopril (25 mg) and candesartan (16 mg) doses were at the top of the relation between dose and renal response.…”
Section: Discussionmentioning
confidence: 99%